Epigenetic Enzyme Mutations: Role in Tumorigenesis and Molecular Inhibitors - Han, Mei; Jia, Lina; Lv, Wencai; Wang, Lihui; Cui, Wei (Frontiers in Oncology, 2019)
Epigenetic modification refers to a heritable change in gene expression without changing the DNA sequence, including DNA methylation and histone modification. Epigenetic regulatory enzymes such as DNA methyltransferase, histone methyltransferase, and histone deacetylase are involved in epigenetic modification. Studies have shown that the dysregulation caused by the changes in the amino acid sequence of these enzymes show closely correlated with the onset and progression of tumor. It has been investigated that some small molecule inhibitors target these aberrant enzymes have shown promising anti-cancer efficacy in preclinical and clinical trials. For example, the small molecule inhibitor ivosidenib, which targets the IDH1 (mutated in R132), has been approved by the FDA for the treatment of acute myeloid leukemia in clinical. Hence, in this review, we summarize the mutation sites of those enzymes in various tumors as well as the tumorigenesis role of them and the candidate target inhibitors, which showing potential therapeutic value. In addition, we further introduce some non-multiple mutation sites of those enzymes, which may be related to the development of tumor and provide support for future study.